2017
DOI: 10.11113/jt.v79.9341
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of Sawdust Concrete

Abstract: Industrialization in developing countries has resulted in an increase in agricultural output and consequent accumulation of unmanageable agro wastes. Pollution arising from such wastes is a matter of concern for many developing nations. The aim of this study is to investigate the behavior of lightweight concrete and the utilization of sawdust as waste material in concrete. This paper focuses on the manufacturing of concrete which possess long duration heat transfer by using sawdust waste. In this research, cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Nowadays, speedy and meteoric development of composite structure stands in need of better concrete performance and a good quality material [1][2][3]. Though concrete is the most cost effective material but it increases dead load of the building due to its high density [4][5][6]. If the density of concrete is reduced it can lead to a number of advantages, as it then results in the reduction of the cost of handling, constructability and transportation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, speedy and meteoric development of composite structure stands in need of better concrete performance and a good quality material [1][2][3]. Though concrete is the most cost effective material but it increases dead load of the building due to its high density [4][5][6]. If the density of concrete is reduced it can lead to a number of advantages, as it then results in the reduction of the cost of handling, constructability and transportation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of building construction, considerable attention and a number of studies in many countries have been devoted to sawdust concrete as a lightweight concrete. In the Singapore-Malaysia region, to use sawdust in building construction many efforts have been exerted to explore its sustainability as sawdust is abundantly present in such tropical regions and is economical and affordable [4].…”
Section: Introductionmentioning
confidence: 99%
“…When cement, sawdust, and sand were combined in the following ratios: 1:1:1, 1:2:1, and 1:3:1 it was found that the 1:3:1 admixture had low thermal conductance compared to the other mix. Because there is more sawdust in the 1:3:1 mixture than in the other two, there is less heat transfer through that mixture [100,109].…”
Section: Thermal Properties Of Sawdust Compositementioning
confidence: 99%
“…Substituting 100% natural aggregate with sawdust increased the sound absorption coefficients from 0.43 to 0.74. This issue can explain by the fact that sawdust provides more interconnecting voids at diverse length scales inside the geopolymer concrete matrix (Memon et al, 2017;Mishra and Jena, 2021). In the high-frequency domain, these permeable materials presented an enhanced sound absorption, especially concerning decreasing the concrete density that led the frequency to change to higher values.…”
Section: Sound Absorptionmentioning
confidence: 99%